2011
DOI: 10.4049/jimmunol.1003081
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TIGIT Has T Cell-Intrinsic Inhibitory Functions

Abstract: Costimulatory molecules regulate the functional outcome of T cell activation, and disturbance of the balance between activating and inhibitory signals results in increased susceptibility to infection or the induction of autoimmunity. Similar to the well-characterized CD28/CTLA-4 costimulatory pathway, a newly emerging pathway consisting of CD226 and T cell Ig and ITIM domain (TIGIT) has been associated with susceptibility to multiple autoimmune diseases. In this study, we examined the role of the putative coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
449
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(483 citation statements)
references
References 14 publications
19
449
2
1
Order By: Relevance
“…Beyond documenting this receptor-ligand interaction and defining the PVR family, it was clearly demonstrated that IL-10 induction via PVR is robust enough to inhibit antigen-specific T-cell responses. Additional studies in which the pathway is inhibited-either by blocking proteins or by gene ablation-support the TIGIT-PVR interaction as being important for setting the threshold for T-cell responses in both secondary lymph organs and mucosal sites (31,32). The predominant immuno-coreceptors on T cells are CTLA-4 and CD28, which engage the same ligands, B7-1 and B7-2, on antigen-presenting cells such as DCs (28,29,33); however, additional receptors, such as PD-1 and ICOS, have emerged as important receptors in the immune system to fine-tune T-cell effector functions and maintain T-cell tolerance (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond documenting this receptor-ligand interaction and defining the PVR family, it was clearly demonstrated that IL-10 induction via PVR is robust enough to inhibit antigen-specific T-cell responses. Additional studies in which the pathway is inhibited-either by blocking proteins or by gene ablation-support the TIGIT-PVR interaction as being important for setting the threshold for T-cell responses in both secondary lymph organs and mucosal sites (31,32). The predominant immuno-coreceptors on T cells are CTLA-4 and CD28, which engage the same ligands, B7-1 and B7-2, on antigen-presenting cells such as DCs (28,29,33); however, additional receptors, such as PD-1 and ICOS, have emerged as important receptors in the immune system to fine-tune T-cell effector functions and maintain T-cell tolerance (34).…”
Section: Discussionmentioning
confidence: 99%
“…PVR, together with TIGIT and other PVRfamily members, CD226 and CD96, similarly regulate immune responses. Engagement of PVR with TIGIT induces an anti-inflammatory response (4,31,32); conversely, PVR interaction with the lower-affinity receptor CD226 on T and NK cells promotes immune activation (19,20). This paradigm holds true for a number of paired, homologous ITIM/ITAM receptors on T and NK cells (35) where the inhibiting receptor has a high affinity and the activating receptor has a lower affinity for the shared binding molecule and implies that the activating receptor probably needs to outcompete the inhibiting interaction to convey a signal.…”
Section: Discussionmentioning
confidence: 99%
“…11 TIGIT-deficient mice are more susceptible to autoimmune diseases. 14,15 However, the inhibitory mechanism mediated by TIGIT has not been elucidated.…”
mentioning
confidence: 99%
“…10,12 TIGIT can bind to PVR of human dendritic cells to enhance interleukin 10 (IL-10) production, which inhibits T-cell activation. 10 Kuchroo et al 14 showed that TIGIT harbors a T-cell-intrinsic inhibitory function to suppress T-cell activation.…”
mentioning
confidence: 99%
“…Furthermore, it is considered a novel immune checkpoint molecule 13. TIGIT negatively regulates T cell responses through the effect of cluster of differentiation (CD) 112 or CD155 on dendritic cells or through intrinsic inhibitory effects such as inhibition of T cell proliferation or suppression of cytokine production in CD4 + T cells 14. Recently, TIGIT + Tregs have been shown to selectively suppress Th1 and Th17 responses but not Th2 responses 15.…”
Section: Introductionmentioning
confidence: 99%